Pengaruh Social Media Marketing, Word of Mouth (WoM) dan Brand Image Terhadap Keputusan Pembelian Smartphone Infinix di Kota Mataram - Muhamad Paris; M. Ilhamuddin (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study aims to determine the influence of Social Media Marketing, Word of Mouth and Brand Image on the purchase decision of Infinix smartphones in Mataram City. The population of this study is all consumers who use smartphones in Mataram City. Data collection in this study used a survey method. The data collection technique uses a questionnaire or online survey technique via Google Form with a questionnaire data collection tool. This study used a sample of 105 people with a purposive sampling method. The type of research used in this study is associative. Data processing in this study uses SPSS by conducting various tests such as Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis Test, t-test, f-test, determination coefficient test. The results of this study indicate that Social Media Marketing has an influence but is not significant on the decision to purchase an Infinix smartphone in the city of Mataram, Word of Mouth has an influence and is significant on the decision to purchase an Infinix smartphone in the city of Mataram, Brand Image has an influence and is significant on the decision to purchase an Infinix smartphone in the City of Mataram.